Pelaksanaan Progam Tahfidzul Qur’an Untuk Meningkatkan Bakat Minat pada Bidang Qur’ani di SD Darul Hikam Bandung - Kinesti, Rakanita Dyah Ayu; Andriani, Rismalinda; Karomah, Puja Sukma Ismul; Innayah, Ivatun Nurul; Basyari, Ahmad Ali; Zahro’, Fatimatuz (MASALIQ, 2022)
This research is motivated by how to implement the Tahfidzul Qur'an extracurricular program at SD Darul Hikam Bandung in increasing the talents and interests of students. The purpose of holding the Tahfidzul Qur'an program is so that students can understand and know the importance of the ability to memorize the Qur'an. The research method used in this research is descriptive qualitative with a focus on principals, vice principals, and those in charge of extracurricular activities as research samples. The data collection techniques used in this study were observation, interviews, and documentation and used data analysis in the form of content analysis. From the results of this study, it was found that the implementation of the Tahfidzul Qur'an extracurricular program at SD Darul Hikam Bandung was carried out once a week, namely on Wednesdays and was carried out starting from the lower grades, namely grade 1 by memorizing chapters 30, and continued chapters 21 to 29 for upper grades. and the conditions that determine graduation at Darul Hikam Elementary School are by memorizing chapter 30. The parties involved in Tahfidz extracurricular activities are the school principal, vice principal, and extracurricular activities supervisor.